(untitled) (Journal of the College of Basic Education, 2024)
The research aims to identify the effect of the (RAP) strategy on the expressive performance of the first intermediate grade female students. In order to achieve the goal of the research, the researchers formulated the following null hypothesis: The two researchers followed the experimental method as it is the appropriate and appropriate method for the nature and purpose of their research, and they chose one of the designs with partial control, which is the design of the control group and the intentional choice with the post-test only.The researchers chose the General Directorate of Education in the Baghdad governorate, Karkh, the third, as a research community from among the six districts of Baghdad governorate. And after the researchers identified the topics of the scientific subject that you will study during the duration of the experiment, which are the topics in the Arabic language book for the first course of the academic year (2021-2022), which amounted to (5 topics).The teaching period lasted (9) weeks, as it started on Tuesday (16/11/2021) and ended on Tuesday (1/11/2022). And to measure the expressive performance of the first-grade average students (the research sample), the researchers prepared a test to measure expressive performance. The researchers tested the students of the two research groups with a post-test. The researchers dealt with the research data and results by using the statistical bag (spss) and by using the following equations test (the t-test) the research resulted in the following results: There is a statistically significant difference at the level of significance (0.05), between the mean scores of the experimental group students and the average scores of the control group in favor of the experimental group.